2014
DOI: 10.1111/gcb.12760
|View full text |Cite
|
Sign up to set email alerts
|

Climatic variability, hydrologic anomaly, and methane emission can turn productive freshwater marshes into net carbon sources

Abstract: Freshwater marshes are well-known for their ecological functions in carbon sequestration, but complete carbon budgets that include both methane (CH4 ) and lateral carbon fluxes for these ecosystems are rarely available. To the best of our knowledge, this is the first full carbon balance for a freshwater marsh where vertical gaseous [carbon dioxide (CO2 ) and CH4 ] and lateral hydrologic fluxes (dissolved and particulate organic carbon) have been simultaneously measured for multiple years (2011-2013). Carbon ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 101 publications
(294 reference statements)
4
43
0
Order By: Relevance
“…Methane emissions from GK Typha-Hydrocharis and GK Carex-Lysimachia were higher compared to a pristine, water saturated sedge fen (dominated by Carex aquatilis) in the southern Rocky Mountains (30 to 34 g CH 4 −C m −2 yr −1 ; Table 6; Wickland et al, 2001) or to Carex acutiformis and Typha latifolia sites during the wet year in the above mentioned rewetted fen grassland (47 and 10 g CH 4 −C m −2 yr −1 , respectively; Günther et al, 2014). They were comparable to temperate Typha latifolia (82 g CH 4 −C m −2 yr −1 ; Whiting and Chanton, 2001) and T. angustifolia marshes (51 g CH 4 −C m −2 yr −1 , Chu et al, 2015; 127 g CH 4 −C m −2 yr −1 , Strachan et al, 2015). The constantly high water levels made us expect a net CO 2 uptake at GK Typha-Hydrocharis and GK CarexLysimachia, as was found for Typha latifolia and T. angustifolia marshes (Whiting and Chanton, 2001;Strachan et al, 2015), for a water saturated temperate sedge fen in the Czech Republic (Dušek et al, 2012), and in the wet year for Carex acutiformis and Typha latifolia (Günther et al, 2014).…”
Section: Annual Co 2 and Methane Balancesmentioning
confidence: 66%
See 2 more Smart Citations
“…Methane emissions from GK Typha-Hydrocharis and GK Carex-Lysimachia were higher compared to a pristine, water saturated sedge fen (dominated by Carex aquatilis) in the southern Rocky Mountains (30 to 34 g CH 4 −C m −2 yr −1 ; Table 6; Wickland et al, 2001) or to Carex acutiformis and Typha latifolia sites during the wet year in the above mentioned rewetted fen grassland (47 and 10 g CH 4 −C m −2 yr −1 , respectively; Günther et al, 2014). They were comparable to temperate Typha latifolia (82 g CH 4 −C m −2 yr −1 ; Whiting and Chanton, 2001) and T. angustifolia marshes (51 g CH 4 −C m −2 yr −1 , Chu et al, 2015; 127 g CH 4 −C m −2 yr −1 , Strachan et al, 2015). The constantly high water levels made us expect a net CO 2 uptake at GK Typha-Hydrocharis and GK CarexLysimachia, as was found for Typha latifolia and T. angustifolia marshes (Whiting and Chanton, 2001;Strachan et al, 2015), for a water saturated temperate sedge fen in the Czech Republic (Dušek et al, 2012), and in the wet year for Carex acutiformis and Typha latifolia (Günther et al, 2014).…”
Section: Annual Co 2 and Methane Balancesmentioning
confidence: 66%
“…However, in contrast to our first hypothesis the sites GK Typha-Hydrocharis and GK Carex-Lysimachia were net CO 2 sources. Similar, a wet sedge fen in the southern Rocky Mountains (Wickland et al, 2001) and a water saturated Typha angustifolia marsh (Chu et al, 2015) were found to be CO 2 sources (Table 6). Chu et al (2015) explain their findings by abnormal climatic conditions.…”
Section: Annual Co 2 and Methane Balancesmentioning
confidence: 70%
See 1 more Smart Citation
“…We could not observe a considerable decrease of the spatial extent of the open water body as emergent vegetation mainly covers the shallower edges of the water body. The effect of water table lowering at Typha sites due to dry conditions is also shown by Günther et al (2015) and Chu et al (2015): relative increase of R eco rates, resulting in net CO 2 release. This might be of special interest in terms of climate change, as a temperature increase and significantly less precipitation in summer are expected for NE Germany and meteorological conditions are more frequently characterised as "unusually" warm and dry.…”
Section: Annual Net Co 2 Releasementioning
confidence: 89%
“…Allochthonous organic matter import into the NE bay due to lateral transport, as discussed for CH 4 , might have further enhanced decomposition (e.g. Chu et al, 2015). Longer data gaps in summer 2013 (see Fig.…”
Section: Annual Net Co 2 Releasementioning
confidence: 97%